Analisis Pengaruh Motivasi Kerja Dan Kedisiplinan terhadap Kinerja Karyawan Bagian Produksi PT. XXX - Rozci, Fatchur; Oktaviani, Dewi Anggun; Lidyana, Novita (Ecobuss, 2024)
This research aims to analyze the influence of Work Motivation and Discipline, simultaneously and partially on the Performance of Production Department Employees at PT. XXX, and determine which of the work motivation and discipline have the dominant influence on the Performance of Production Department Employees at PT. XXX. This research uses quantitative methods. The population used is employees of the production department of PT. XXX. Sampling used Purposive Sampling Technique with the criteria: employees are permanent employees and are more than 20 years old with more than one year of service. The sample in this study amounted to 46 respondents. The data collection techniques used were questionnaires and interviews. The data analysis technique used is Multiple Linear Regression. From the research that has been carried out, it can be seen that there is a simultaneous influence between the variables Work Motivation (X1) and Deficiency (X2) on performance (Y) as evidenced by the Fcount value of 23,289 with a significance level of 0.000. Partially, work motivation (X1) and dedication (X2) also influence performance (Y), as evidenced by the t-count value of the work motivation variable of 2,441 with a significance level of 0.000 and the t-count value of the discipline variable of 2,215 with a significance level of 0.000. The Work Motivation variable (X1) has a dominant influence on employee performance (Y) as evidenced by the Standardized Coefficients Beta value of the Work Motivation variable (X1) of 0.261 which is greater than the Discipline variable (X2) of 0.151.